Bortezomib‐Encapsulated Dual Responsive Copolymeric Nanoparticles for Gallbladder Cancer Targeted Therapy. Issue 7 (23rd January 2022) - Chen, Mingyu; Juengpanich, Sarun; Li, Shijie; Topatana, Win; Lu, Ziyi; Zheng, Qiang; Cao, Jiasheng; Hu, Jiahao; Chan, Esther; Hou, Lidan; Chen, Jiang; Chen, Fang; et al.
Abstract: Gallbladder cancer (GBC) is a rare but the most malignant type of biliary tract tumor. It is usually diagnosed at an advanced stage and conventional treatments are unsatisfactory. As a proteasome inhibitor, bortezomib (BTZ) exhibits excellent antitumor ability in GBC. However, the long‐term treatment efficacy is limited by its resistance, poor stability, and high toxicity. Herein, BTZ‐encapsulated pH‐responsive copolymeric nanoparticles with estrone (ES‐NP(BTZ; Ce6) ) for GBC‐specific targeted therapy is reported. Due to the high estrogen receptor expression in GBC, ES‐NP(BTZ; Ce6) can rapidly enter the cells and accumulate near the nucleus via ES‐mediated endocytosis. Under acidic tumor microenvironment (TME) and 808 nm laser irradiation, BTZ is released and ROS is generated by Ce6 to destroy the "bounce‐back" response pathway proteins, such as DDI2 and p97, which can effectively inhibit proteasomes and increase apoptosis. Compared to the traditional treatment using BTZ monotherapy, ES‐NP(BTZ; Ce6) can significantly impede disease progression at lower BTZ concentrations and improve its resistance. Moreover, ES‐NP(BTZ; Ce6) demonstrates similar antitumor abilities in patient‐derived xenograft animal models and five other types of solid tumor cells, revealing its potential as a broad‐spectrum antitumor formulation. Abstract : Tumor‐pH‐sensitive self‐assembled polymeric nanoparticles with estrone tumor‐targeting ligand for gallbladder cancer‐targeted treatment (bortezomib‐encapsulated nanoparticles with estrone ES‐NP(BTZ; Ce6) ) are developed. Bortezomib inhibits the proteasomes, whereas the generated ROS damages the "bounce‐back" response proteins to inhibit new proteasome production. ES‐NP(BTZ; Ce6) can effectively treat gallbladder cancer via enhanced proteasome dysfunction at reduced bortezomib concentrations while mitigating systemic toxicity both in vitro and in vivo.